Riscos geomorfológicos e hidrológicos em Aracaju - Santos, Alizete dos (2012)
The urbanization process in Brazil is characterized by its fast and disorderly drivingthe occupation of houses in fragile physical environments characterized as the use and occupation. This dynamic puts the population, especially low purchasing power in a situation of environmental risks they are hydrological and / or geomorphological features. The risk is that the probability of loss and / or damage to the social and environmental point of view which the population is exposed. In this context, the present study was to examine the environmental risks physical geomorphological and hydrological and consolidated in the urban expansion area of Aracaju in the prevention of accidents. To achieve this and other proposed objectives was made using different procedures, focusing initially the literature survey and mapping for the systematization of the knowledge produced on the subject in various sources and public institutions, in addition to field work to show and record the risks geomorphological and hydrological. The methodology used allowed the crossing of the environmental variables considered basic to identify the level of vulnerability in Aracaju. The investigative analysis shows that in the places of occurrence of the events / accidents dominate the standard urban periphery, except in the expansion area of the municipality. Floods and flooding are common in many locations mainly in expansion and in the more consolidated, as well as near the drainage channels, whether natural or rectified. The areas with the greatest evidence of geomorphological hazards Floods and flooding are common in many locations mainly in expansion and in the more consolidated, as well as near the drainage channels, whether natural or rectified. The areas with the greatest evidence of geomorphological hazards (erosion and mass movements) are tied to insecurity or lack of basic infrastructure, mainly present in the Santa Maria neighborhoods, Jabotiana, America, Cidade Nova, Port Dantas / Coqueiral and Soledade. The absence of detailed studies and a plan to manage environmental risks in difficult decision making framework for ensuring the combat and / or mitigation of environmental risks in Aracaju. Therefore, it is necessary that the Government undertake preventive actions to avoid the uncontrolled growth of the city, as of works of sanitation, to ensure the safety population, and the development and implementation of structural measures (technical control) and non-structural (prevention plans and alerts, risk zoning, flood insurance) to combat the risk